2015
DOI: 10.1021/acsnano.5b01495
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ambipolar GaSb/InAs Core–Shell Nanowires by Thermovoltage Measurements

Abstract: In semiconductor heterostructures with a type II band alignment, such as GaSb-InAs, conduction can be tuned from electron- to hole-dominated using an electrostatic gate. However, traditional conductance measurements give no direct information on the carrier type, and thus limit the ability to distinguish transport effects originating from the two materials. Here, we employ thermovoltage measurements to GaSb/InAs core-shell nanowires, and reliably identify the dominant carrier type at room temperature as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Thermoelectric transport in CSNs has been already studied in a couple of experimental papers. One recent work was the characterization of GaAs/InAs nanowires by thermovoltage measurements in those situations when electrical conductance does not provide information [30]. Another study demonstrated enhanced thermoelectric properties in Bi/Te CSNs via strain effects [31].…”
mentioning
confidence: 99%
“…Thermoelectric transport in CSNs has been already studied in a couple of experimental papers. One recent work was the characterization of GaAs/InAs nanowires by thermovoltage measurements in those situations when electrical conductance does not provide information [30]. Another study demonstrated enhanced thermoelectric properties in Bi/Te CSNs via strain effects [31].…”
mentioning
confidence: 99%
“…Starting with the conductance trace as a function of back-gate voltage [Fig. 3(c)], we observe that the InAs reference nanowire (green) becomes depleted for negative gate voltages, whereas the core-shell nanowire (blue) shows ambipolar behavior as a result of an onset of hole transport in the GaSb shell for V g < 0 V. 24 Charge stability diagrams were recorded for both devices, and they are shown in Figs. 3(d)-(f).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the QWs, InAs/GaSb core-shell nanowires (NWs) have been investigated both experimentally and theoretically. [5][6][7][8][9][10][11][12][13][14][15] Core-shell NWs with one shell are grown by several groups today, [8][9][10][11][12][13][14][15][16] and NWs with two shells can be grown, 16 e.g., for the reason of a passivating outer layer on InAs. 14 In this work we study core-shell-shell NWs, where an insulator core is radially overgrown with one InAs and one GaSb layer, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…BHZ parameters used in Fig.2(b). The rest of the parameters appearing in Eqs (9)(10)(11)(12). are set to zero.…”
mentioning
confidence: 99%